PTU-327 An evaluation of the effect of using an acetic acid protocol for the detection of dysplasia in barrett's oesophagus in a district general hospital setting. (22nd June 2015) - Ghuman, S; Asghar, K; Evans, J; Kakhi, S; Hawkes, N
Abstract : Introduction: Studies have suggested that mucosal enhancement techniques, such as acetic acid (AA) spray may increase detection of advanced dysplasia during surveillance of Barrett's oesophagus. A standardised AA protocol was adopted by 3 consultants and a nurse endoscopist (NE) from 2011, other endoscopists continued a conventional methodology for surveillance. We aimed to investigate the impact of the use of a standard protocol (HD image in WL, FICE assessment and use of 3% AA dye spray, with targeted biopsies and Seattle protocol biopsies) on the detection of all dysplasia and advanced dysplasia (HGD, or in-situ adenocarcinoma). Method: We searched the HICCS Endoscopic Reporting System for all endoscopies where Barrett's oesophagus was detected between October 2010 and October 2014 (n = 587). Only specific surveillance cases were included (index and specific recall cases excluded). Endoscopy reports were checked and histology results retrieved from the Welsh Clinical Portal system. Differences in dysplasia detection rates for the AA Protocol (AA) or 'standard' white light endoscopy (WLE) were tested using the Chi-squared test, with significance level set at p < 0.05. Results: In the 4 year study period, 367 Barrett's surveillance procedures were performed in 220 patients. The AA protocol was applied during 86 procedures, standard WLE in 269 procedures. The dysplasia rates are shown in the Table 1 . There was a significant increase in the detection rate of all types of dysplasia (p < 0.00001), and advanced dysplasia (p = 0.007) in the AA protocol group. Dysplasia detection rates achieved by the trained NE were comparable with consultants using AA protocol and higher than consultant and NE colleagues not using AA protocol. Conclusion: Introduction of a Standard AA Protocol in our Health Board was associated with higher detection of dysplasia compared with white light endoscopies performed during the same time interval. The training of a nurse endoscopist to provide this service has proved both feasible and effective. All surveillance patients now attend pre-booked lists where AA protocol is used. Disclosure of interest: None Declared.